Potential associations between the mite Varroa destructor and other stressors in honeybee colonies (Apis mellifera L.) in temperate and subtropical climate from Argentina - Giacobino, Agostina (2018)
The presence of Varroa destructor in colonies of Apis mellifera is explained by the interaction among a number of factors including beekeeping practices and surrounding environment features. The aim of this study was to evaluate the relative impact of environment geographical region and beekeeping management on Varroa infestation levels throughout a year. A monitoring study was carried out during 2015 in north-central regions from Argentina, consisting of three sampling dates: 1) autumn survey before autumn acaricide treatment; 2) autumn survey after autumn acaricide treatment and 3) spring survey. During these visits, we collected samples for Varroa mites and Nosema sp. presence assessment and information concerning the apiary management practices during each period. Both regional location and beekeeping practices impact on V. destructor infestation level during the course of the year, but relative importance depend partially on the time of year when this was observed. Varroa infestation level is driven simultaneously by a wide-range of environmental factors (regional effect) and honeybee population dynamics. Additionally, colony life histories are also strongly affected by the management practices employed by beekeepers, especially regarding the Varroa mites control and the supplementary feeding. Complexity involving multiple factors interaction in socio-ecological systems like beekeeping is discussed.